6. Oblicz: a) 10-6 + 8 = d) 24:6. (-2) = 10 - (6 + 8) = 24:06. (-2)) = b) 10-5 - 6 = e) -12 +4:2-8= (10 - 5). 6 = (-12 + 4): 2-8 = c) 8. 7-6 = f) 11 -8:4-10 = 8. (7-6) = (11-8):(4 - 10) =​



6 Oblicz A 106 8 D 246 2 10 6 8 2406 2 B 105 6 E 12 428 10 5 6 12 4 28 C 8 76 F 11 8410 8 76 1184 10 class=

Odpowiedź :

R00sxe

a) 10-6 + 8 = 12

10 - (6+8) = 10 - 14 = -4

b) 10 - 5 x 6 = 10 - 30 = -20

8 x (7-6) = 8 x 1 = 8

c) 8 x 7 - 6 = 56 - 6 = 50

8 x (7-6) = 8 x 1 = 8

d) 24 : 6 x (-2) = 4 x (-2) = -8

24 : (6 x (-2) = 24 : -12 = -2

e) -12 + 4 : 2 - 8 = -12 + 2 - 8 = -18

(-12 + 4) : 2 - 8 = -8 : 2 - 8 = -4 - 8 = -12

f) 11 - 8 : 4 - 10 = 11 - 2 - 10 = -1

(11 - 8) : (4 - 10) = 3 : -6 = -0,5